Hypoxic stress and hypoxia-inducible factors in leukemias - Magliulo, Daniela; Bernardi, Rosa (Frontiers in Oncology, 2022)
To cope with hypoxic stress, ancient organisms have developed evolutionally conserved programs centered on hypoxia-inducible transcriptional factors (HIFs). HIFs and their regulatory proteins have evolved as rheostats to adapt cellular metabolism to atmospheric oxygen fluctuations, but the amplitude of their transcriptional programs has tremendously increased along evolution to include a wide spectrum of physiological and pathological processes. The bone marrow represents a notable example of an organ that is physiologically exposed to low oxygen levels and where basal activation of hypoxia signaling appears to be intrinsically wired within normal and neoplastic hematopoietic cells. HIF-mediated responses are mainly piloted by the oxygen-labile  subunits HIF1 and HIF2, and current literature suggests that these genes have a functional specification that remains to be fully defined. Since their identification in the mid 90s, HIF factors have been extensively studied in solid tumors, while their implication in leukemia has lagged behind. In the last decades however, many laboratories have addressed the function of hypoxia signaling in leukemia and obtained somewhat contradictory results. Suppression of HIFs expression in different types of leukemia has unveiled common leukemia-promoting functions such as stimulation of bone marrow neoangiogenesis, maintenance of leukemia stem cells and chemoresistance. However, genetic studies are revealing that a definition of HIF factors as bona fide tumor promoters is overly simplistic, and, depending on the leukemia subtype, the specific oncogenic event, or the stage of leukemia development, activation of hypoxia-inducible genes may lead to opposite consequences. With this article we will provide an updated summary of the studies describing the regulation and function of HIF1 and HIF2 in blood malignancies, spanning from acute to chronic, lymphoid to myeloid leukemias. In discussing these data, we will attempt to provide plausible explanations to contradictory findings and point at what we believe are areas of weakness in which further investigations are urgently needed. Gaining additional knowledge into the role of hypoxia signaling in leukemia appears especially timely nowadays, as new inhibitors of HIF factors are entering the clinical arena for specific types of solid tumors but their utility for patients with leukemia is yet to be determined.